Effects of Levamisole on Sexual Behavior, Reproductive Hormones and Testicular Histopathology in Male Rats - Mulayim, Sefa; Yardimci, Ahmet; Tektemur, Nalan Kaya; Tektemur, Ahmet (Wiley, 2022)
[Abstract Not Available]
Keywords: COVID-19; FSH; Levamisole; LH; Sexual Behavior